High Frequency In vitro Regeneration of Gynura procumbens (Lour.) Merr. (Plant Tissue Culture and Biotechnology, 2017)
An efficient rapid in vitro regeneration protocol was described from nodal segment, leaf and petiole explants. MS medium supplemented with 1.0 mg/l BAP and 0.5 mg/l IAA was found best for the multiple shoot formation from nodal segments. In this combination 99% explants produced multiple shoots and the average number of shoots per explants was 20.1 ± 1.96. For petiole and leaf explants best response was observed on MS supplemented with 2.0 mg/l BAP, 1 mg/l IAA and 0.5 mg/l Kn. Petiole explants produced highest mean number of shoots/explant (22.9 ± 1.728) among the three explants when the explants were cultured on MS with 2.0 mg/l BAP, 1 mg/l IAA and 0.5 mg/l Kn. The highest frequency of root induction (100%) and mean number of roots/plantlets (11.75) were obtained on MS. The rooted plantlets were transferred for hardening following acclimatization and finally were successfully established in the field.Plant Tissue Cult. & Biotech. 27(2): 207-216, 2017 (December)